Towards using UAV for improving 5G cellular communication systems - Mohamed El Sayed Kotb; Wagdy R. Anis; Ahmed A. Abd-Elhafez (Institute of Advanced Engineering and Science, 2021)
Unmanned aerial vehicles (UAVs) have sparked a lot of interest in the wireless networking community as an emerging subject in aerial robotics. The UAV environment can be used to improve UAV communications in various ways. These smart devices cater for a broad variety of wireless technologies and applications because of UAV's inherent features related to versatile mobility in 3D space, autonomous operations as well as intelligent positioning. This study will investigate the convergence synergies between 5G/B5G mobile systems and UAV technologies, with the UAV being integrated into current cellular networks as a modern aerial user equipment (UE). In this integration, UAVs play the function of cellular flying customers, and are hence referred to as cellularly linked UAVs (a.k.a. UAVUE, drone-UE, 5G-connected drone, or aerial user). The major goal of this research is to provide a thorough analysis of the integration task, as well as major technical breakthroughs from 5G/B5G and current work in prototyping architecture and field trials that support cell-based UAVs. This study examines recent 3GPP standards advances as well as socio-economic challenges that must be addressed before this promising technology can be properly implemented. There are already some accessible issues clearing the way for potential study opportunities.